Employee Engagement Mediates Self-Efficacy and Perceived Organizational Support on Nurses’ Organizational Citizenship Behavior - Sulaimiah; Sarifudiin Serif; Harmi Widiana; Zira Wahyu (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Human resources are vital to organizational success, especially in healthcare, where psychological and organizational factors influence service quality. This study examines how self-efficacy and perceived organizational support affect organizational citizenship behavior through employee engagement among nurses at health centers. The study aims to determine whether engagement mediates the relationship between self-efficacy, perceived organizational support, and organizational citizenship behavior. Using a quantitative causal associative design, data were collected from 89 nurses and analyzed through validity and reliability tests, classical assumption tests, and path analysis, with t-tests and Sobel tests to assess direct and indirect effects. Results show that self-efficacy and perceived organizational support significantly enhance employee engagement and organizational citizenship behavior, while engagement mediates both relationships. The findings confirm the role of engagement as a psychological bridge connecting self-efficacy and organizational support to positive extra-role behavior. Health institutions should improve nurses’ self-efficacy through training, mentoring, and recognition programs while maintaining strong organizational support to foster engagement and encourage cooperative, high-quality service behavior.